Analisa Gugus Fungsi Komposit Adsorben Berbahan Spent Bleaching Earth (SBE) Dan Spent Mushroom Substrate (SMS) - Husni, Afdaul; Yenie, Elvi; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Spent Bleaching Earth (SBE) is a solid waste generated in the stages of the process of purification of oil in the vegetable oil industry, while the Spent mushroom substrate (SMS) is one of the waste biomass resulting from the production of mushrooms. The second material is the waste that has been tdik used anymore, and if not used back can cause environmental pollution. This study aims to determine the functional groups of the composite adsorbent using the method of FTIR spectra with the variation of the composition of the SBE-SMS 25: 75 %. Composite that has been made then were characterized by the methods of FTIR to analyze the cluster function. FTIR analysis of the composite adsorbent after the test FTIR known to the presence of hydroxyl group (O-H), cluster C=O (ketone, amide, ester, carboxyl and aromatic compounds), phosphate groups (P-OH), a cluster of aluminum silica (Si-O-Al) and cluster siloxane (Si-O-Si).Key words: Composite, FTIR, Spent Bleaching Earth, And Spent Mushroom Substrate.